What about extra adaptions and special support in Swedish School Age Educare Centers? - Boström, Lena; Elvstrand, Helene (Frontiers in Education, 2025)
This study’s background is the lack of research and knowledge about special education in Sweden’s School-Age Educare Centers (SAEC), focusing on extra adaptations and special support. The study is important for international educational research because it draws attention to a research area that is lacking. Additionally, out-of-school programs are beginning to question and develop the field of special education. The study aimed to determine to what extent staff of various professional groups support students in need of special support and extra adaptations in SAEC. It is based on a web survey with 412 responses from SAEC staff. The empirical material was analyzed with descriptive and inferential statistics. As a theoretical frame, we used the relational perspective. The result shows that various professional groups have different and distinctive perceptions of students needing special support and extra adaptations in SAEC, especially the principals. Another result was that few students have action programs in SAEC. The results suggest that the students do not receive the special educational support needed to attain sufficient development and learning in the SAEC, which does not meet the governing documents for the SAEC. This study makes an important contribution for all professionals in SAEC (or internationally similar after-school settings) because staff is predicted to receive increased importance in the SAEC to compensate and supplement schools. Implications for practice are the need to allocate resources to implement the special education reform, prioritize SAEC and support staff in the implementation.